(untitled) (World Bulletin of Education and Learning, 2025)
The contemporary goal of language education has shifted from mere grammatical accuracy to the development of robust intercultural communicative competence (Byram, 1997). This necessitates an approach that moves beyond the traditional four-skills model to integrate the cultural nuances, social practices, and pragmatic norms of the target language community—collectively known as linguaculture (Agar, 1994). This article argues that the Problem-Based Learning (PBL) approach is uniquely positioned to foster this enhanced linguocultural skillset. Through its core principles of student-centered inquiry, collaborative problem-solving, and engagement with authentic, contextualized problems, PBL creates a dynamic learning environment where language and culture are not taught in isolation but are acquired as an integrated, meaningful whole. This paper will delineate the theoretical underpinnings of PBL, illustrate its application in the language classroom through practical examples, and synthesize evidence demonstrating its efficacy in developing learners’ cultural awareness, pragmatic competence, and symbolic competence (Kramsch, 2006). The conclusion will affirm that PBL is not merely a pedagogical tool but a vital framework for preparing learners for real-world intercultural interactions.